PEMBANGUNAN EKONOMI MELALUI PARIWISATA PADA PESTA BUDAYA ERAU DI TENGGARONG, KABUPATEN KUTAI KARTANEGARA, PROVINSI KALIMANAN TIMUR - Ignatius Kurniawan (Prodi Ilmu Administrasi Negara, 2015)
The aim of this resarch is to know the development of the regional on tourism by Erau as a traditional event in Tenggarong, Kutai Kartanegara Regency, East Kalimantan Province in the prespective of the economy. The method of it is by library research which had been done from January to March 2015. The result of it that the tourism can encourage the economy of the region. The econmic point of view is that the tourism can open the labour opportunity for examples : transportation, accomodation and consumption. The transportation consists of local and regional and international. The accomudation can support the business of hotel, cottage and villa. The consumption can share the profit for restaurant, coffee-house and the market.